Multi‐omic rejuvenation of naturally aged tissues by a single cycle of transient reprogramming. Issue 3 (2nd March 2022) - Chondronasiou, Dafni; Gill, Diljeet; Mosteiro, Lluc; Urdinguio, Rocio G.; Berenguer‐Llergo, Antonio; Aguilera, Mònica; Durand, Sylvere; Aprahamian, Fanny; Nirmalathasan, Nitharsshini; Abad, Maria; Martin‐Herranz, Daniel E.; Stephan‐Otto Attolini, Camille; et al.
Abstract: The expression of the pluripotency factors OCT4, SOX2, KLF4, and MYC (OSKM) can convert somatic differentiated cells into pluripotent stem cells in a process known as reprogramming. Notably, partial and reversible reprogramming does not change cell identity but can reverse markers of aging in cells, improve the capacity of aged mice to repair tissue injuries, and extend longevity in progeroid mice. However, little is known about the mechanisms involved. Here, we have studied changes in the DNA methylome, transcriptome, and metabolome in naturally aged mice subject to a single period of transient OSKM expression. We found that this is sufficient to reverse DNA methylation changes that occur upon aging in the pancreas, liver, spleen, and blood. Similarly, we observed reversion of transcriptional changes, especially regarding biological processes known to change during aging. Finally, some serum metabolites and biomarkers altered with aging were also restored to young levels upon transient reprogramming. These observations indicate that a single period of OSKM expression can drive epigenetic, transcriptomic, and metabolomic changes toward a younger configuration in multiple tissues and in the serum. Abstract : A single cycle of transient OSKM activation in naturally aged mice is able to partially reverse age‐associated changes in several tissues. Specifically, we could capture reversion of alterations occurring with aging at the level of DNA methylation, transcription, as well as, serum metabolome. These changes were stable for a period of up to four weeks after OSKM cessation.